Recriminalization in the New Criminal Code Against the Criminal Justice System Article on Information and Electronic Transactions - Heri Nalom Opung Sunggu; Muhammad Syukran Yamin Lubis (Fox Justi : Jurnal Ilmu Hukum, 2026)
The results of the discussion conclude that the principle of recriminalization or regulation of new criminal acts that were previously not clearly regulated or new articles related to computer crimes and electronic transactions as well as related to the criminal justice system and law enforcement policies to balance the interests of law enforcement of electronic transactions. This shows that the new Criminal Code attempts to combine the principle of substantive justice while maintaining criminal law as a last resort in resolving legal conflicts. The research method used is normative juridical, with a literature study of the New Criminal Code, national legal literature, and scientific articles discussing the principle of ultimum remedium and Criminal Code reform.